Juan Pablo II y su Magisterio - Mendoza Valdebenito, Jorge (Veritas, 2005)
Pope John Paul II's teaching embraced many topics ni numerous documents. This article si a proposal ot systematise his thought regarding wt o axes: on one side, those documents concerning man and society, and, on an other side, the ones related to the mission and caling ofthe Church.